Towards a better climate treaty - Scott Barrett (Fondazione Eni Enrico Mattei (FEEM), 2002)
The essential problem with the Kyoto approach is that it provides poor incentives for participation and compliance. The minimum participation clause is set at such a low level that the agreement can enter into force while limiting the emissions of less than a third of the global total. The compliance mechanism, negotiated years after the emission limits were agreed upon, essentially requires that non-complying countries punish themselves for failing to comply––a provision that is unlikely to influence behavior. The likely outcome will be an agreement that fails to enter into force, or an agreement that enters into force but is not implemented, or an agreement that enters into force and is implemented but only because it requires that countries do next to nothing about limiting their emissions. These weaknesses cannot be improved by a minor redesign of the treaty. The basic problem stems from the requirement that countries agree to, and meet, emission limitation ceilings––the most central element of the Kyoto Protocol.My proposal focuses on collective funding of basic research into the development of new, carbon-saving energy technologies, and on standards protocols for the adoption and diffusion of new technologies around the world. The main attraction of this approach is strategic: it does not require that compliance be enforced, and it provides positive incentives for participation. It is not an ideal remedy to global climate change, but the principle of sovereignty means that an ideal remedy does not exist for this problem.
Keywords: Q20; 330; Kyoto Protocol; compliance and participation in international environmental agreements; technology standards; cooperative R&D; Umweltabkommen; Klimaschutz; Welt